Modelling of high impedance faults in distribution systems and validation based on multiresolution techniques. (May 2020) - Torres-Garcia, Vicente; Guillen, Daniel; Olveres, Jimena; Escalante-Ramirez, Boris; Rodriguez-Rodriguez, Juan R.
Abstract: The electric arc phenomenon associated with high impedance faults (HIFs) in distribution systems is an exciting subject that directly impacts over the reliability of electrical utilities, because fault currents are very small and present non-linearity and asymmetrical waveforms. Therefore, HIFs may be an undetectable phenomenon by overcurrent protections like fuses, re-closers, and relays. A HIF entails a challenge for its detection and location. In this sense, more realistic high impedance models, as well as reliable signal processing techniques, are needed to extract all transient characteristics aiming to detect HIFs in distribution networks. In this work, an efficient Resistive-HIF model is proposed and implemented into the Alternative Transients Program of the Electromagnetic Transients Program (ATP/EMTP) software to represent the main characteristics of HIFs. The model is compared against well-prove models by using two multiresolution approaches based on the Hermite transform and the Wavelet transform considering different frequency bands.